LATIHAN MENELAN PADA PASIEN STROKE DENGAN GANGGUAN MENELAN DI RUANG KENANGA RUMAH SAKIT TK II DUSTIRA CIMAHI - Dewi Safariah, Triana; Kusmawati, Dessi; Nur Salwa, Dita (Jurnal Kesehatan An-Nuur, 2025)
The prevalence of stroke at Dustira Hospital is 124 people. Stroke is a sudden neurological function deficit caused by a disturbance in cerebral blood circulation. One of its signs and symptoms is swallowing disorder. If swallowing exercises are not performed, complications such as aspiration pneumonia may occur. Swallowing exercises are a type of therapy designed to improve swallowing ability by focusing on strengthening muscles and enhancing the coordination of nerves and muscles involved in the swallowing process. This case study uses a descriptive method to illustrate nursing care for stroke patients experiencing swallowing disorders. The instruments used include the standard operating procedure for swallowing exercises and an observation sheet before and after the exercises. The assessment results showed that the patient had difficulty moving the tongue to the right, left, and upward, impaired swallowing reflexes, slurred speech, and frequent choking while eating or drinking, leading to the nursing diagnosis of swallowing disorder. Swallowing exercises were conducted three times a day for seven days, with each session lasting 30 minutes. The evaluation of this case showed that the swallowing disorder initially had a swallowing reflex score of 3 (moderate), which improved to 4 (fair improvement) after the intervention. It is concluded that swallowing exercises can improve the swallowing reflex in stroke patients with swallowing disorders. It is hoped that these exercises can be applied by hospitals, patients, and families independently.